If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3(x + 5) = 1 + -4x Reorder the terms: 4x + -3(5 + x) = 1 + -4x 4x + (5 * -3 + x * -3) = 1 + -4x 4x + (-15 + -3x) = 1 + -4x Reorder the terms: -15 + 4x + -3x = 1 + -4x Combine like terms: 4x + -3x = 1x -15 + 1x = 1 + -4x Solving -15 + 1x = 1 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -15 + 1x + 4x = 1 + -4x + 4x Combine like terms: 1x + 4x = 5x -15 + 5x = 1 + -4x + 4x Combine like terms: -4x + 4x = 0 -15 + 5x = 1 + 0 -15 + 5x = 1 Add '15' to each side of the equation. -15 + 15 + 5x = 1 + 15 Combine like terms: -15 + 15 = 0 0 + 5x = 1 + 15 5x = 1 + 15 Combine like terms: 1 + 15 = 16 5x = 16 Divide each side by '5'. x = 3.2 Simplifying x = 3.2
| 3c+4c-12=6+c | | 4(X-9)=3(X-8) | | 3X-420=0 | | 3x+4-5x=2-4x | | 13x-9=3x+10 | | yx(420)=3x | | 4x-7(3x+6)=4x-9 | | 5+3=810 | | 20x=8(x+180) | | 48-3x=5x | | 70-3x=4x | | xy=420 | | 4x+1=3x+3 | | 25-2x=3x+20 | | 9+9x=17+5x | | 6x+6=4+8x | | 7x+9=3+9x | | p+np= | | 9x+8=7x+6 | | 2x-34=-20 | | 8y-3x=-49 | | 6x-1=36x+2 | | 7x+16=-5 | | 6(2z+3)-2z=-5(z-2)+2 | | 73-5x=38 | | g(x)=6x^2+13x+6 | | 0.6x-2.3=4.3 | | 25x^2+1=0 | | 7=-3(4+m)-2m | | a(1+21a)=10 | | 65-5x=4x+19 | | 2(x+4)-1=-3 |